2022
DOI: 10.1128/spectrum.02484-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of a Novel H16N3 Virus Isolated from a Migratory Gull in China in 2021 and Animal Studies of Infection

Abstract: Migratory wild birds are natural reservoirs of H16 viruses and play a key role in the global prevalence of these viruses. Here, we found that H16 viruses predominantly circulate in migratory gulls and that the gull H16N3 virus cannot replicate efficiently in chickens, ducks, or mice without prior adaptation. These findings contribute to our understanding of the ecology, evolution, and biological properties of H16 viruses and will guide avian influenza surveillance in birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The YRD wetland located in Eastern China is an important habitat for migratory birds on the East Asian-Australasian (EAA) flyway. We have identified 28 subtypes of AIVs in wild birds in YRD wetland from 2017 to 2022, as shown in our previous studies [8,9,[30][31][32][33][34][35]. In this study, we fully uncovered the ecology and evolutionary dynamics of the globally identified H12 viruses.…”
Section: Introductionsupporting
confidence: 56%
“…The YRD wetland located in Eastern China is an important habitat for migratory birds on the East Asian-Australasian (EAA) flyway. We have identified 28 subtypes of AIVs in wild birds in YRD wetland from 2017 to 2022, as shown in our previous studies [8,9,[30][31][32][33][34][35]. In this study, we fully uncovered the ecology and evolutionary dynamics of the globally identified H12 viruses.…”
Section: Introductionsupporting
confidence: 56%
“…It has been confirmed that wild birds are closely related to the occurrence and spread of various poultry infectious diseases, including avian influenza and Newcastle disease ( Ziedler and Hlinak, 1992 ; Rahman et al, 2018 ; Verhagen et al, 2021 ; Graziosi et al, 2022 ). Migratory wild birds have played a crucial role in the extensive geographical dissemination of avian influenza, with multiple outbreaks being closely associated with viruses carried by these migratory species ( Bi et al, 2015 ; Krauss et al, 2015 ; Li et al, 2021 ; Wang et al, 2022 ; Zhao et al, 2022 ). The highly pathogenic H5N1, H5N6 and H5N8 viruses carried by migratory birds have caused multiple epidemics in Eurasia and North America ( Lee et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%